2016
DOI: 10.1007/s12273-016-0310-7
|View full text |Cite
|
Sign up to set email alerts
|

Particle transport characteristics in indoor environment with an air cleaner: The effect of nonuniform particle distributions

Abstract: Air cleaners are expected to improve the indoor air quality by removing the gaseous contaminants and fine particles. In our former work, the effects of the air cleaner on removing the uniformly distributed particles were numerically investigated. Based on those results, this work further explores the performances of the air cleaner in the reduction of two nonuniform particle distributions generated by smoking and coughing. The Lagrangian discrete trajectory model combined with the Eulerian fluid method is empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 24 publications
(36 reference statements)
1
11
0
Order By: Relevance
“…This approach not only enhances the efficiency of the PAC but also minimizes potential dispersion and recirculation of infectious droplets within the immediate environment. This is consistent with the conclusions obtained by Chen et al [23] who noted that the orientation of the air cleaner had impact on its performance. And they also found that more particles were removed by the air cleaner when it was placed with a face-to-face layout as particles were more likely to join the main flow of the circulating airflow.…”
Section: The Influence Of the Opening Configuration Of Pac On Droplet...supporting
confidence: 93%
See 2 more Smart Citations
“…This approach not only enhances the efficiency of the PAC but also minimizes potential dispersion and recirculation of infectious droplets within the immediate environment. This is consistent with the conclusions obtained by Chen et al [23] who noted that the orientation of the air cleaner had impact on its performance. And they also found that more particles were removed by the air cleaner when it was placed with a face-to-face layout as particles were more likely to join the main flow of the circulating airflow.…”
Section: The Influence Of the Opening Configuration Of Pac On Droplet...supporting
confidence: 93%
“…where u pi is the velocity component of the droplet; å F i denotes the sum of all external forces on the droplet in the i direction; F , drag i , F g i , and F a i , are drag force, gravity force and additional force respectively. The additional forces on the droplet include the pressure gradient force, virtual mass force, Bassett force, Brownian force, thermophoretic force and Saffman force, etc [23]. In indoor environment, the pressure gradient force, virtual mass force and Bassett force are much less than drag force and have a sufficiently small effect on the droplet motion to be negligible [37].…”
Section: Discrete Phase Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…When airborne particles were distributed uniformly indoors, the flow rate had the greatest impact on the indoor particle concentration, and the position of the air cleaner affected the particle concentration at low volumetric flow rates; little difference was found between the effects of horizontal and upward ejection ( Jin et al., 2016 ). By contrast, under non-uniform aerosol distributions, caused by smoking and coughing, the position of the air cleaner significantly impacted the particle concentration, which was also affected by the expiratory airflow velocity and the orientation of the air cleaner ( Chen et al., 2017 ). When the PACs were applied in wards, Mousavi et al.…”
Section: Infection Control Strategiesmentioning
confidence: 99%
“…Then, the amount of pollutant removed by air cleaners depends on the concentration distribution of the pollutants, resulting in a nonlinear phenomenon. Therefore, although optimal operating conditions for air cleaners have been studied based on comparisons through experiments and computational fluid dynamics models, [11][12][13][14] it is unclear why these conditions are optimal.…”
Section: Introductionmentioning
confidence: 99%